2005
DOI: 10.1097/00006416-200507000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Interventions to Enhance Osteoporosis Prevention in Women

Abstract: Tailored interventions increased women's perceived barriers to calcium and exercise. Both groups increased calcium intake. The mixed findings of increased perception of barriers to calcium and exercise and decreased exercise behaviors indicate the need for further study. This important intervention has implications for orthopaedic nurses and healthcare professionals involved in health promotion and prevention of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 18 publications
5
75
0
1
Order By: Relevance
“…This review supports the notion that osteoporosis education with BMD is more effective at influencing calcium and vitamin D intake than education alone and the more abnormal the bone density the more significant the increase in calcium and vitamin D intake (Estok et al, 2007;Rolnick et al, 2001;Sedlak et al, 2005). However, the influence of education and BMD on exercise is non-conclusive (Estok et al, 2007;Wallace et al, 2004) having no influence on increasing exercise and in fact knowing bone density may have a negative influence, lowering participation in exercise (Rolnick et al, 2001;Sedlak et al, 2005). …”
Section: Overviewsupporting
confidence: 68%
See 2 more Smart Citations
“…This review supports the notion that osteoporosis education with BMD is more effective at influencing calcium and vitamin D intake than education alone and the more abnormal the bone density the more significant the increase in calcium and vitamin D intake (Estok et al, 2007;Rolnick et al, 2001;Sedlak et al, 2005). However, the influence of education and BMD on exercise is non-conclusive (Estok et al, 2007;Wallace et al, 2004) having no influence on increasing exercise and in fact knowing bone density may have a negative influence, lowering participation in exercise (Rolnick et al, 2001;Sedlak et al, 2005). …”
Section: Overviewsupporting
confidence: 68%
“…Even though, the increase in calcium intake and vitamin D was statistically significant with abnormal BMD measurements, overall the findings indicate that increasing generalized osteoporosis knowledge does directly influence calcium and vitamin D intake (Estok et al, 2007;Rolnick et al, 2001;Sedlak et al, 2005) suggesting that a lack of knowledge acts as a barrier and constrains participation with OPBs. This finding is also supported by a recent survey examining barriers to calcium supplementation for women 20-64 years of age, the survey suggested that one of the primary reasons women, 55% in this survey, have high rates of non-use of supplementation was not knowing it was necessary (Tyler et al, 2008).…”
Section: Osteoporosis Knowledge Gapmentioning
confidence: 77%
See 1 more Smart Citation
“…One of the challenges of such a program was seen in the sustainability of such change and a need for long-term additional support initiatives. To our knowledge, tailored educational programs in osteoporosis addressed lifestyle changes in the prevention of osteoporosis, but not the issue of drug adherence [15][16][17][18][19] . Although the value of the educational support program presented by Nogues et al 8 is probably evident, there remains a need for high quality studies that compare the effectiveness of programs enhancing adherence to osteoporosis medications.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Evaluation designs for assessing impact of these nurse interventions include pre-/postintervention designs with or without controls, as well as randomized controlled trials (RCTs). Durations of health outcome assessments range from several months to a year or more.…”
Section: Original Research and Contributionsmentioning
confidence: 99%